THE FUTURE POLICY OF SUSTAINABLE PLASTIC WASTE MANAGEMENT IN SOUTH KALIMANTAN PROVINCE - Ifrani Ifrani; Muhammad Ali Amrin (Al-Adl : Jurnal Hukum, 2021)
Plastic waste management is currently a major problem in several countries, especially in Indonesia. Because plastic waste cannot be decomposed. In South Kalimantan which is a wetland area, plastic waste is a serious problem that must be handled by the local government, due to the nature of wetlands that have a high water content or are inundated by water, either permanently or seasonally. The Non-decomposition of plastic waste will destroy wetlands. The specific objectives to be achieved are: (1) The legal policies that local governments take manage plastic waste in South Kalimantan. (2) The ideal future policy of plastic waste management to preserve the sustainability of wetlands. The method used to compile this research is doctrinal legal research. Legal research here does not merely examine the law as a statutory rule but also examines how the law has a positive effect on people's lives. The result shows that in drafting future policy/law the viewpoint must be established that the policy direction of the ius constituendum is not only aimed at providing protection of the right to the environment for humans but also changing the environmental paradigm and outlook towards Ecocentrism and Deep Ecology rather than the views of Anthropocentrism and Shallow Ecology.